Strategi Pemasaran Melalui Swot Analisys Dalam Meningkatkan Daya Saing Pada Rumah Sakit Permata Hati Lamongan : Marketing Strategy Through SWOT Analysis to Enhance Competitiveness at Permata Hati Hospital, Lamongan - Nur Adinda Qurrotul Aini; Sukaris Sukaris (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2026)
This study aims to analyze the marketing strategy of Permata Hati Lamongan Hospital in enhancing competitiveness through a SWOT Analysis approach. The research employed a descriptive qualitative method with data collection techniques including interviews, observations, and documentation. The analysis was conducted by identifying internal factors (strengths and weaknesses) as well as external factors (opportunities and threats) influencing the hospital’s marketing performance. The results indicate that the hospital possesses several strengths, including strong local branding, humanistic services, partnerships with BPJS and private insurance providers, and the availability of healthcare service packages. However, several weaknesses were identified, such as suboptimal digital promotion, inconsistent updates of doctors’ schedules, and the absence of a dedicated marketing team. Opportunities that can be leveraged include the use of social media, collaboration with educational institutions and agencies, and support from government health programs. Meanwhile, threats include intense competition among healthcare facilities, changes in patient behavior relying on digital reviews, and increasingly strict health promotion regulations. Based on the SWOT analysis, SO, WO, ST, and WT strategies were formulated as recommendations to strengthen marketing and improve competitiveness. The study concludes that strengthening digital marketing, developing technology-based service innovations, and improving information management are strategic steps that need to be implemented to address the increasingly complex dynamics of competition in the healthcare industry.